Differentiated approach to the choice of the acetabular component at total hip replacement in patients with dysplastic hip arthritis - Loskutov, Oleg; Loskutov, Oleksandr; Furmanova, Ksenia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
After the total hip arthroplasty in patients with dysplastic hip arthritis (DHA), the number of complications associated with implant instability, in particular, the acetabular component, remains high. Objective: to develop the concept of differentiated choice of acetabular component at different stages of process with national modular implants ORTEN. Methods: 322 patients with DHA (394 total hip arthroplasty) were examined. According to Crowe classification, DHA I degree was detected in 40 (12.4 %) cases, II — 142 (44.1 %), III — 126 (39 %), IV — 14 (4.4 %). A severe degree of DHA was defined in 282 (87.6 %) patients. Modular implants ORTEN were used in 361 (91.6 %) cases, Zimmer — in 24 (6.1 %), Stryker — in 9 (2.3 %). Results: in order to work out the concept of differentiated choice of acetabular component in patients with DHA, we evaluated the degree of deformation, depth of the acetabulum, the possibility to achieve the primary and secondary stability of the acetabular component. We designed and certified the modular implants ORTEN with screwed or press-fit acetabular component, or with cemented type of fixation. Non cemented acetabular component of small sizes are designed. Threaded projections of screwed acetabular component provide high stability of fixation in cases with segmental and central defects of acetabulum. Indications to apply at DHA — II, III and IV degrees, I — with concomitant osteoporosis. Acetabular component, with press-fit fixation were used in cases of DHA I and II degrees without significant segmental defects. Cement cups were used in patients with DHA with concomitant osteoporosis. Revision surgeries due to acetabular component instability in the period of 1–10 years were made in 18 (4.6 %) patients: with screwed acetabular component — 11 (3.4 %), with those that were press-fit — 7 (13.7 %). Conclusions: press-fit acetabular component, are better to use in the cases of DHA I and II degrees in the absence of large bone defects; screwed — in cases of osteopenia and osteoporosis, DHA II and III degrees, in cases of deepening of the acetabulum bottom and mediation of acetabular component.